The effect of synthesis and thermal treatment on phase composition and ionic conductivity of Na-doped SrSiO3 - Pandey R.; Viviani M.; Singh P.; Botter R.; Carpanese M.P.; Barbucci A.; Presto S. (My University, 2025)
The structural and electrochemical properties of Sr1-xNaxSiO3 were studied. Powders with different compositions (0.1 ≤ x ≤ 0.45) were prepared by solid state reaction. Mixing of SrCO3, Na2CO3 and SiO2 was carried out in different media in order to explore the effect of solvents on the formation of secondary phases. X-ray diffraction was employed to study the phase composition of mixtures treated in air at different temperatures in the range 850–1050 °C for at least 12 h. Various heating schemes were applied to help the incorporation of Na in the monoclinic SrSiO3 structure. Pressed pellets were sintered at 1000 °C for at least 12 h and electroded with Ag paste for electrochemical characterization. For most compositions and thermal treatments, the formation of the insulating Na2Si2O5 phase was observed, as reported in literature. Highest conductivity and degradation rate was obtained when synthesis was carried out in acetone with single calcination step at 850 °C, due to the crystallization of Na2Si2O5 from glass. Double calcination limited conductivity but increased its thermal stability. When ethanol was used for powder mixing and double calcination was applied, the material exhibited higher conductivity after long term ageing at 650 °C, also thanks to its low activation energy, without appreciable crystallization of other silicates. © 2017 Elsevier B.V.